2022
DOI: 10.1155/2022/1016495
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Clinical and Histopathological Diagnoses in Oral Cavity Lesions: A 12-Year Retrospective Study

Abstract: Objective. Proper diagnosis plays a key role in the treatment and prognosis of all diseases. Although histopathological diagnosis is still known as the gold standard, final diagnosis becomes difficult unless precise clinical descriptions are obtained. So, this study aimed to evaluate the concordance of the clinical and histopathological diagnoses of all oral and maxillofacial biopsy specimens in a 12-year duration. Materials and Methods. Archive files and clinical findings related to 3001 patients who had been… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
3
1
0
7
Order By: Relevance
“…The findings of this research show a strong relationship between the concordance rate of histopathological and clinical diagnosis and the kind of lesion. This conclusion is comparable with those of Saravani et al [18,19] , who discovered a substantial relationship between the type of lesion (neoplastic or non-neoplastic) and clinicopathological concordance. Saravani et al [18] divided lesions into five main groups, with exophytic lesions being the most prevalent.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this research show a strong relationship between the concordance rate of histopathological and clinical diagnosis and the kind of lesion. This conclusion is comparable with those of Saravani et al [18,19] , who discovered a substantial relationship between the type of lesion (neoplastic or non-neoplastic) and clinicopathological concordance. Saravani et al [18] divided lesions into five main groups, with exophytic lesions being the most prevalent.…”
Section: Discussionsupporting
confidence: 91%
“…This study revealed slight female predominance (54.8% versus 45.2% males). Similar findings were reported in Saudi Arabia (Jeddah (18), South-Western-Jazan (19), and Eastern Province (20), Iran (21)(22)(23), Turkey (24), and in North Iraq; Sulaimani (6) and Erbil (4). A higher percentage of female distribution was recorded in Jordan (60%).…”
Section: Discussionsupporting
confidence: 85%
“…In Erbil, Yekin et al( 4) study showed that most patients are in their second to fourth decades of life. Siadati et al (21) study showed more biopsied lesions in less than 40 years old with a mean age of 34.6 ± 20.3 years, and in Farzinnia et al (23) study in Sheraz-Iran, more frequent lesions were in the second decade of life (10-19 years). A Turkish study showed a nearly similar mean age of the studied patients (39.26 ±17.89 years) (24).…”
Section: Discussionmentioning
confidence: 91%
“…In the present study, around 10% of all biopsied lesions in the orofacial region involved the tongue similar to a report from Iran [13]. On the contrary, the prevalence was higher than reports from Nigeria [4] and Iran [12] but lower than findings from Turkey [7] and India [9].…”
Section: Discussionsupporting
confidence: 81%